Modified nanometer titanium dioxide for cosmetics, preparation method, cosmetic composition and application

CN122916205APending Publication Date: 2026-10-16MAANSHAN COSMOS CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510416395.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本申请提供一种化妆品用改性纳米二氧化钛、制备方法、化妆品组合物及应用,以解决现有技术中添加有二氧化钛的化妆品难以兼顾防晒性和使用感的问题

Benefits of technology

[0025] Fourthly, this application also provides the application of the modified nano-titanium dioxide described in the first aspect or the modified nano-titanium dioxide prepared by the method described in the second aspect in increasing the sun protection value in sunscreen cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916205A_ABST
    Figure CN122916205A_ABST
Patent Text Reader

Abstract

The application provides modified nanometer titanium dioxide for cosmetics, a preparation method, a cosmetic composition and application. The modified nanometer titanium dioxide comprises a nanometer titanium dioxide body and a first coating layer and a second coating layer which are sequentially coated on the nanometer titanium dioxide body. The first coating layer is an inorganic coating, and the second coating layer is an organic coating. The grain size of the modified nanometer titanium dioxide is 12-16 nm, the modified nanometer titanium dioxide has a rod structure, and the length-diameter ratio of the titanium dioxide is 3.5-4.2:1. The application uses nanometer titanium dioxide with a specific size, can more effectively block ultraviolet rays, and improves the sunscreen performance. The sequential coating of the inorganic coating and the organic coating makes the modified nanometer titanium dioxide have excellent hydrophobicity. The modified nanometer titanium dioxide provided by the application has excellent hydrophobicity and ultraviolet absorption, good dispersibility in oily solvents, improves the sunscreen performance of cosmetics, and also has excellent use feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cosmetic technology, and in particular to a modified nano-titanium dioxide for cosmetics, its preparation method, cosmetic composition, and its application. Background Technology

[0002] Nano titanium dioxide is a white, loose powder widely used in numerous fields due to its strong UV shielding ability, good dispersibility, and weather resistance. The main crystal forms of nano titanium dioxide are anatase and rutile. Anatase nano titanium dioxide is a commonly used photocatalyst, used in wastewater treatment to degrade organic pollutants in water through photocatalytic reactions. Rutile nano titanium dioxide, with its stable properties, high refractive index, and relatively low photocatalytic activity, has become an ideal inorganic UV shielding agent. In the field of sunscreen cosmetics, it effectively blocks UV damage to the skin, protecting it from photoaging and other problems. In industries such as chemical fibers, plastics, rubber, and coatings, adding nano titanium dioxide can improve the weather resistance of products and extend their service life.

[0003] Currently, the preparation of nano-titanium dioxide involves surface modification of titanium dioxide particles by coating them with substances to improve their properties. Performance improvement is achieved by controlling the coating amount and coating layer. The coating process involves complex reaction conditions, such as temperature, concentration, pH, and reaction time. Even slight changes in these conditions can significantly affect the coating effect. Therefore, different companies use different processes to prepare titanium dioxide, resulting in inconsistent product quality and thus affecting its performance in cosmetics.

[0004] In pursuit of high SPF ratings, nano-titanium dioxide may be added in high doses during cosmetic manufacturing. Excessive titanium dioxide content can result in a rough texture, affecting application evenness and leading to an uneven protective layer on the skin. This reduces sun protection effectiveness and negatively impacts both user experience and aesthetics. Secondly, the hydrophobicity and dispersibility of cosmetics are also crucial. Poor hydrophobicity leads to poor dispersibility, making the product prone to agglomeration. High-titanium dioxide products, when applied, can cause a white cast, a heavy feel, and an unnatural appearance due to powder agglomeration. Therefore, cosmetics containing nano-titanium dioxide often struggle to balance sun protection and user experience. Improving the sun protection performance of nano-titanium dioxide products while maintaining a superior user experience remains a pressing issue. Summary of the Invention

[0005] The present application provides modified nano-titanium dioxide for cosmetics, a preparation method thereof, a cosmetic composition and an application, so as to solve the problem that cosmetics added with titanium dioxide in the prior art are difficult to balance sun protection performance and use feeling.

[0006] In a first aspect, the present application provides modified nano-titanium dioxide for cosmetics, the modified nano-titanium dioxide comprises a nano-scale titanium dioxide body, and a first coating layer and a second coating layer sequentially coated on the nano-scale titanium dioxide body, the first coating layer is an inorganic coating material, and the second coating layer is an organic coating material;

[0007] The modified nano-titanium dioxide has a grain size of 12 to 16 nm, the modified nano-titanium dioxide has a rod-like structure, and the aspect ratio of the modified nano-titanium dioxide is 3.5 to 4.2:1.

[0008] In the modified nano-titanium dioxide for cosmetics provided by the present application, the major axis and minor axis of the titanium dioxide are smaller, and the grain size is smaller. The grain size of the nano-titanium dioxide is far less than 1 / 10 of the wavelength of incident ultraviolet rays, which can more effectively block ultraviolet rays and improve the sun protection performance. After the organic coating material with a hydrophobic long-chain structure is coated on the surface of titanium dioxide, the modified nano-titanium dioxide is endowed with excellent hydrophobicity. At the same time, the inorganic coating layer can reduce the agglomeration tendency between titanium dioxide particles, and the organic coating layer enhances its compatibility in oily media, so that the modified nano-titanium dioxide can be uniformly dispersed in the oily components of cosmetics. Therefore, when the modified nano-titanium dioxide provided by the present application is used in cosmetic products, it not only improves the sun protection performance, but also has an excellent use feeling.

[0009] In some possible implementations, the major axis d1 of the rod-like structured modified nano-titanium dioxide ranges from 30<d1≤37 nm, and the minor axis d2 of the rod-like structured modified nano-titanium dioxide ranges from 7<d2≤10 nm.

[0010] In some possible implementations, the mass fraction of the inorganic coating material is 7 to 8%, and the mass fraction of the organic coating material is 7 to 9%.

[0011] In some possible implementations, the mass fraction of the inorganic coating material is 7.4 to 7.7%, and the mass fraction of the organic coating material is 7.7 to 7.8%.

[0012] In some possible implementations, the grain size of the modified nano-titanium dioxide is 14 to 15 nm.

[0013] In some possible implementations, the crystal form of the modified nano-titanium dioxide is anatase, rutile or amorphous.

[0014] In some possible implementations, the inorganic coating is selected from one or more of aluminum hydroxide, aluminum oxide, silicon oxide, or zirconium oxide.

[0015] In some possible implementations, the organic coating is selected from stearic acid, isostearic acid, palmitic acid, or behenic acid.

[0016] Secondly, this application provides a method for preparing modified nano-titanium dioxide for cosmetic use, wherein the modified nano-titanium dioxide is the modified nano-titanium dioxide described in the first aspect, and the method includes:

[0017] At 35–45°C, titanium tetrachloride aqueous solution is added dropwise to an alkaline solution until the pH of the reaction solution is neutral, at which point the addition of titanium tetrachloride aqueous solution is stopped; the alkaline solution is an aqueous solution of alkali metal hydroxide with a mass concentration of 12–15%;

[0018] The reaction solution was heated to 85-95°C, and titanium tetrachloride aqueous solution was added to it. The reaction was then kept at the temperature to obtain nano-sized titanium dioxide dispersion.

[0019] An alkaline solution was added to the nano-sized titanium dioxide dispersion to adjust the pH value of the dispersion to neutral. After filtration, washing, and drying, the nano-sized titanium dioxide bulk was obtained.

[0020] The nano-sized titanium dioxide bulk was mixed with an aqueous solution of inorganic coated metal water-soluble salt and then subjected to a coating reaction. After filtration and washing, inorganic coated titanium dioxide particles were obtained.

[0021] The inorganic-coated titanium dioxide particles are mixed with an organic coating or its salt and then subjected to a coating reaction. The mixture is then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0022] The inorganic coated metal water-soluble salt is selected from one or more of the following: sodium aluminate, sodium aluminate, aluminum trichloride, aluminum sulfate, sodium silicate, zirconium sulfate, zirconium chloride, or zirconium nitrate.

[0023] In some possible implementations, the process of mixing the nano-sized titanium dioxide bulk with an aqueous solution of an inorganically coated metal water-soluble salt and then performing a coating reaction includes: after the reaction is completed, cooling the solution to room temperature and then performing multiple filtrations and washings to obtain inorganically coated titanium dioxide particles.

[0024] Thirdly, this application provides a cosmetic composition comprising the modified nano-titanium dioxide described in the first aspect, a skin moisturizer, an emulsifier, a humectant, a dispersant, a suspending agent, a film-forming agent, a stabilizer, a preservative, an antioxidant, a skin feel improver, a skin conditioning agent, and water; wherein the mass fraction of each component in the cosmetic composition ranges as follows: modified nano-titanium dioxide 1-25%, skin moisturizer 26-70%, emulsifier 1-8%, humectant 0-8%, dispersant 0-2.5%, suspending agent 0-5%, film-forming agent 0-5%, stabilizer 0-1.5%, preservative 0-1%, antioxidant 0-1%, skin feel improver 0-10%, skin conditioning agent 0-8%, and the balance being water.

[0025] Fourthly, this application also provides the application of the modified nano-titanium dioxide described in the first aspect or the modified nano-titanium dioxide prepared by the method described in the second aspect in increasing the sun protection value in sunscreen cosmetics.

[0026] Fifthly, this application also provides the application of modified nano-titanium dioxide prepared by the method described in the first aspect or the method described in the second aspect in sunscreen cosmetics to increase hydrophobicity.

[0027] As described above, this application provides a modified nano-titanium dioxide for cosmetics, a preparation method, a cosmetic composition, and its application. The modified nano-titanium dioxide comprises a nano-sized titanium dioxide matrix and a first coating layer and a second coating layer sequentially coating the nano-sized titanium dioxide matrix. The first coating layer is an inorganic coating, and the second coating layer is an organic coating. The modified nano-titanium dioxide has a grain size of 12-16 nm, a rod-like structure, and an aspect ratio of 3.5-4.2:1. By using 12-16 nm nano-titanium dioxide, this application can more effectively block ultraviolet rays and improve sun protection performance. Compared to titanium dioxide of other shapes, the rod-like structure with an aspect ratio of 3.5-4.2:1 can form a denser and more effective ultraviolet scattering network when arranged. Rod-shaped particles with different orientations can scatter ultraviolet rays from multiple angles, further enhancing the shielding effect against ultraviolet rays. The sequential coating with inorganic and organic coatings alters the original hydrophilic surface properties of titanium dioxide, giving the modified nano-titanium dioxide excellent hydrophobicity. The dual effect of the inorganic and organic coatings effectively improves the dispersibility of titanium dioxide in the medium. The modified nano-titanium dioxide for cosmetics provided in this application exhibits excellent hydrophobicity and UV absorption, lipophilicity, and good dispersibility in oily solvents, enhancing the sun protection performance of cosmetics while also providing a superior user experience. Attached Figure Description

[0028] To more clearly illustrate the technical solution of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 Electron micrograph of modified nano-titanium dioxide for cosmetics prepared in the example of this application. Detailed Implementation

[0030] The embodiments described in the following examples do not represent all embodiments consistent with this application. They are merely examples of systems and methods consistent with some aspects of this application as detailed in the claims.

[0031] Currently, the preparation of nano-titanium dioxide involves surface modification of the titanium dioxide by coating it with substances to improve its properties. Performance improvement is achieved by controlling the coating amount and coating layer. The coating process involves complex reaction conditions, such as temperature, concentration, pH, and reaction time. Even slight changes in these conditions can significantly affect the coating effect. Therefore, different companies use different processes to prepare titanium dioxide, resulting in inconsistent product quality and thus affecting its performance in cosmetics.

[0032] In pursuit of high SPF ratings, nano-titanium dioxide may be added in high doses during cosmetic manufacturing. Excessive titanium dioxide content can result in a rough texture, affecting application evenness and leading to an uneven protective layer on the skin, thus reducing sun protection effectiveness. Secondly, besides sun protection performance, the user experience of cosmetics is also crucial; poor hydrophobicity can cause product aggregation and poor dispersion, resulting in a white cast, a heavy feel, and an unnatural appearance. Therefore, cosmetics containing nano-titanium dioxide in related technologies struggle to balance user experience and sun protection. Thus, improving the sun protection performance of titanium dioxide products while maintaining an excellent user experience remains a pressing issue.

[0033] Based on this, and addressing the problem that existing cosmetics containing titanium dioxide struggle to balance sun protection and user experience, this application provides a modified nano-titanium dioxide for cosmetics, its preparation method, a cosmetic composition, and its application. This titanium dioxide has smaller major and minor axes and smaller grain size. While meeting the European Union Scientific Committee on Consumer Safety (SCCS) requirements for the aspect ratio of nano-titanium dioxide, the grain size is significantly smaller than 1 / 10 of the incident ultraviolet wavelength, enabling more effective UV blocking and improved sun protection performance. Coating the surface of titanium dioxide with an organic coating possessing a hydrophobic long-chain structure imparts excellent hydrophobicity to the modified nano-titanium dioxide. Simultaneously, the inorganic coating layer reduces the tendency for aggregation between titanium dioxide particles, improving photostability, while the organic coating layer enhances its compatibility in oily media, allowing the modified nano-titanium dioxide to be uniformly dispersed in the oily components of cosmetics.

[0034] In some embodiments, this application provides a modified nano-titanium dioxide for cosmetic use, the modified nano-titanium dioxide comprising a nano-sized titanium dioxide body and a first coating layer and a second coating layer sequentially coating the nano-sized titanium dioxide body, wherein the first coating layer is an inorganic coating and the second coating layer is an organic coating.

[0035] The modified nano-titanium dioxide has a grain size of 12–16 nm, a rod-like structure, and an aspect ratio of 3.5–4.2:1.

[0036] The grain size of the modified nano-titanium dioxide is 12 to 16 nm, which is far less than 1 / 10 of the wavelength of incident ultraviolet rays. According to the Rayleigh Scattering Theory, the modified nano-titanium dioxide will undergo isotropic scattering, and the scattering intensity is nearly proportional to the sixth power of the particle size. Due to its small grain size, the modified nano-titanium dioxide has stronger Rayleigh scattering for medium-wave ultraviolet rays (UVB band, 290 to 320 nm), which can block ultraviolet rays more effectively and improve sun protection performance. Titanium dioxide with a rod-like structure and an aspect ratio of 3.5 to 4.2:1 can form a denser and more effective ultraviolet scattering network when arranged, compared with titanium dioxide of other shapes. Rod-like titanium dioxide with different orientations can scatter ultraviolet rays from multiple angles, further enhancing the ultraviolet shielding effect. The first coating layer formed by the inorganic coating can improve the surface properties of titanium dioxide, reduce the negative impact caused by photocatalytic activity, and simultaneously enhance the reflection and scattering capabilities for ultraviolet rays. The second coating layer of the organic coating can further optimize the dispersibility of titanium dioxide in oily systems, enabling it to be distributed more uniformly in sunscreens, improving the absorption and scattering efficiency of ultraviolet rays, thereby enhancing the overall sun protection effect. In some embodiments, the grain size of the modified nano-titanium dioxide is 12nm, 13nm, 14nm, 15nm, 16nm. In some embodiments, the aspect ratio of the modified nano-titanium dioxide is 3.88 to 4.12:1.

[0037] In some embodiments, the grain size of the modified nano-titanium dioxide is 14 to 15 nm.

[0038] At the grain size of 14 to 15 nm, the interaction force between the modified nano-titanium dioxide particles is relatively balanced, and van der Waals force and electrostatic force will not cause excessive agglomeration of the particles. In the oily or aqueous system of sunscreens, the titanium dioxide of the above size can be uniformly dispersed to form a stable dispersion system, without phenomena such as precipitation and delamination, which ensures the stability of the product during storage and use. In emulsion-type sun protection products, titanium dioxide always maintains a uniformly dispersed state, ensuring that the texture and performance of the product are consistent at each use, and there will be no situation where the upper layer is thin and the lower layer is thick.

[0039] In some embodiments, the long diameter d1 of the rod-shaped modified nano-titanium dioxide ranges from 30 < d1 ≤ 37 nm, and the short diameter d2 of the rod-shaped modified nano-titanium dioxide ranges from 7 < d2 ≤ 10 nm.

[0040] According to light scattering theory, the specific ratio between the major and minor axes of modified nano-titanium dioxide and the wavelength of ultraviolet light allows light to undergo multiple scattering and reflection when it encounters titanium dioxide particles, thus greatly enhancing its ability to block ultraviolet light. The appropriate size of the major and minor axes balances the van der Waals forces and electrostatic forces between particles, reducing particle aggregation. In oil-based systems, the rod-shaped modified nano-titanium dioxide can be uniformly dispersed, forming a stable dispersion system. In cosmetic formulations, its excellent dispersibility ensures a uniform product texture, smooth application, and prevents a grainy feel or sedimentation. Specifically, the major axis d1 can be 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, or 37nm. The minor axis d2 can be 8nm, 9nm, or 10nm.

[0041] In some embodiments, the inorganic coating has a mass fraction of 7-8%, and the organic coating has a mass fraction of 7-9%.

[0042] In this application, when the inorganic coating content is set to 7-8% by mass, a coating layer of suitable thickness can be formed on the surface of titanium dioxide. Taking aluminum hydroxide as an example, the coating layer at the above proportion can enhance the reflection and scattering of ultraviolet rays. An appropriate amount of aluminum hydroxide coating will not result in insufficient protection due to insufficient coating, nor will it negatively affect the optical properties of titanium dioxide itself due to excessive coating. When the organic coating content is 7-9% by mass, it works synergistically with the inorganic coating. Organic coatings, such as stearic acid, with their long-chain structure, can optimize the dispersibility of titanium dioxide in oily systems, allowing titanium dioxide to be more evenly distributed in sunscreen cosmetics, fully utilizing its ability to absorb and scatter ultraviolet rays, and further improving the sun protection effect. 7-8% of the inorganic coating first modifies the surface of titanium dioxide, laying the foundation for subsequent organic coating. The inorganic coating layer can change the surface charge and properties, facilitating the tight bonding of the organic coating. 7-9% of the organic coating, with its long-chain hydrophobic groups, forms a highly efficient hydrophobic layer. In some embodiments, the inorganic coating has a mass fraction of 7.4–7.7%, and the organic coating has a mass fraction of 7.7–7.8%.

[0043] In some embodiments, the titanium dioxide is in the form of anatase, rutile, or amorphous. In some embodiments, the titanium dioxide is in the form of rutile.

[0044] Rutile titanium dioxide has a high refractive index, which gives it a strong ability to reflect and scatter ultraviolet (UV) radiation, especially UVB (290–320 nm) and UVA (320–400 nm). In personal sunscreens, it effectively blocks UV rays, reducing skin damage and preventing sunburn, tanning, and photoaging.

[0045] In some embodiments, the inorganic coating is selected from one or more of aluminum hydroxide, aluminum oxide, silicon oxide, or zirconium oxide.

[0046] Coatings such as aluminum hydroxide, alumina, silicon dioxide, and zirconium oxide can form a physical barrier on the surface of titanium dioxide, inhibiting the recombination of photogenerated carriers, reducing free radical generation, and lowering photocatalytic activity. This ensures sun protection effectiveness while improving product safety and stability. Simultaneously, inorganic coatings can alter the surface charge and properties of titanium dioxide, reducing the tendency for particle aggregation. For example, after titanium dioxide is coated with silicon dioxide, the silanol groups on its surface can form hydrogen bonds or other interactions with the surrounding medium, increasing the repulsive force between particles. This makes titanium dioxide easier to disperse evenly in aqueous or oil-based systems, forming a stable dispersion system, avoiding precipitation and stratification, and ensuring stable product quality. During storage and use, the stably dispersed titanium dioxide can continue to perform its function. In sunscreen cosmetics, this ensures consistent sun protection performance with each use.

[0047] In some embodiments, the organic coating is selected from stearic acid, isostearic acid, palmitic acid, or behenic acid.

[0048] Organic coatings such as stearic acid, isostearic acid, palmitic acid, or behenic acid all have long-chain alkyl structures. The chemical structure of stearic acid is CH3(CH2). 16 COOH, isostearic acid, palmitic acid, and behenic acid are similar. Long-chain alkyl groups are hydrophobic groups, and when they coat the surface of titanium dioxide, they form a hydrophobic layer on the particle surface. When sunscreen cosmetics come into contact with water, this hydrophobic layer can effectively prevent water from contacting titanium dioxide, making it difficult for water to easily wet the particles, thereby significantly improving the hydrophobicity of titanium dioxide.

[0049] In some embodiments, this application provides a method for preparing modified nano-titanium dioxide for cosmetic use, wherein the modified nano-titanium dioxide is the modified nano-titanium dioxide provided in the above embodiments, and the method includes:

[0050] At 35–45°C, titanium tetrachloride aqueous solution is added dropwise to an alkaline solution until the pH of the reaction solution is neutral, at which point the addition of titanium tetrachloride aqueous solution is stopped; the alkaline solution is an aqueous solution of alkali metal hydroxide with a mass concentration of 12–15%;

[0051] The reaction solution was heated to 85-95°C, and titanium tetrachloride aqueous solution was added to it. The reaction was then kept at the temperature to obtain nano-sized titanium dioxide dispersion.

[0052] An alkaline solution was added to the nano-sized titanium dioxide dispersion to adjust the pH value of the dispersion to neutral. After filtration, washing, and drying, the nano-sized titanium dioxide bulk was obtained.

[0053] The nano-sized titanium dioxide bulk was mixed with an aqueous solution of inorganic coated metal water-soluble salt and then subjected to a coating reaction. After filtration and washing, inorganic coated titanium dioxide particles were obtained.

[0054] The inorganic-coated titanium dioxide particles are mixed with an organic coating or its salt and then subjected to a coating reaction. The mixture is then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0055] This application allows for more precise microscopic control of the crystal form and grain size of titanium dioxide by setting different process temperatures, enabling the acquisition of high-purity target crystal forms of specific sizes for application in the cosmetics field. This application combines inorganic and organic coatings to obtain modified nano-titanium dioxide that combines hydrophobicity and dispersibility, allowing it to disperse uniformly in oil-based systems such as sunscreen cosmetics, thus improving product quality. The titanium dioxide modified by inorganic and organic coatings exhibits superior sun protection performance; its efficient scattering and absorption of ultraviolet rays significantly improves the sun protection factor (SPF) of sunscreen products.

[0056] In some embodiments, the alkaline aqueous solution is one or more of alkali metal hydroxide aqueous solutions, such as sodium hydroxide aqueous solution and / or potassium hydroxide aqueous solution; the concentration of the alkaline aqueous solution is 12-15 wt%.

[0057] In some embodiments, the solvent for adjusting the pH value is hydrochloric acid, sulfuric acid, sodium hydroxide, potassium hydroxide, or ammonia.

[0058] In some embodiments, the inorganic coated metal water-soluble salt is selected from one or more of the following: sodium aluminate, sodium aluminate, aluminum trichloride, aluminum sulfate, sodium silicate, zirconium sulfate, zirconium chloride, or zirconium nitrate.

[0059] The process of mixing nano-sized titanium dioxide bulk with an aqueous solution of inorganically coated metal water-soluble salt and then carrying out a coating reaction includes: after the reaction is completed, cooling the solution to room temperature and then filtering and washing it multiple times to obtain inorganically coated titanium dioxide particles.

[0060] Compared with the conventional process, in the present application, after the surface of titanium dioxide is coated with an inorganic coating material, the reacted solution is filtered and thoroughly washed. Adding a washing step in the process and thoroughly washing the solution can effectively remove impurity ions introduced during the inorganic coating process, such as incompletely reacted metal salt ions, residual ions of pH regulators, and the like. If these impurity ions remain in the product, they will interfere with the crystal structure and surface properties of titanium dioxide. After removing the impurities, the adverse effect on the photocatalytic activity of titanium dioxide can be reduced, and its stability and effect in applications such as sun protection can be improved. During the inorganic coating process, residual salts will affect the integrity and uniformity of the subsequent organic coating, thereby further affecting the hydrophobic performance of the surface of the modified nano-titanium dioxide; after these salts are removed by thorough washing, the organic coating material can bind to the surface of titanium dioxide more tightly and effectively. Taking stearic acid as an example of the organic coating material, the washed surface is more conducive to the directional arrangement of the long-chain hydrophobic groups of stearic acid, forming a complete and effective hydrophobic layer, thereby improving the hydrophobicity of the product.

[0061] Since temperature plays a key role in the grain size and morphology of titanium dioxide, the present application adopts two process temperatures for preparing the nano-scale titanium dioxide bulk, which are 35 to 45°C and 85 to 95°C respectively.

[0062] In the low-temperature stage of 35 to 45°C, the reaction rate is relatively slow, which is conducive to the slow formation of crystal nuclei, and avoids the excessively small grain size and uneven distribution caused by a large number of crystal nuclei being rapidly generated. In the high-temperature stage of 85 to 95°C, sufficient energy is provided for crystal growth, so that the crystal grains can grow at an appropriate rate. Through the synergistic effect of these two temperature stages, titanium dioxide particles with a grain size of 12 to 16 nm can be finally obtained, which exhibit a rod-like morphology, with a major diameter d1 of 30 < d1 ≤ 37 nm, a minor diameter d2 of 7 < d2 ≤ 10 nm, and an aspect ratio of 3.5 to 4.2:1. This specific grain size and morphology endow titanium dioxide with excellent optical performance, which has high-efficiency scattering capacity for ultraviolet rays and improves the sun protection performance.

[0063] In some embodiments, the present application provides a cosmetic composition, comprising the modified nano-titanium dioxide in the above embodiments, an emollient, an emulsifier, a humectant, a dispersant, a suspending agent, a film-forming agent, a stabilizer, a preservative, an antioxidant, a skin feel improver, a skin conditioning agent and water; wherein, the mass fraction ranges of each component of the cosmetic composition are: 1-25% of modified nano-titanium dioxide, 26-70% of emollient, 1-8% of emulsifier, 0-8% of humectant, 0-2.5% of dispersant, 0-5% of suspending agent, 0-5% of film-forming agent, 0-1.5% of stabilizer, 0-1% of preservative, 0-1% of antioxidant, 0-10% of skin feel improver, 0-8% of skin conditioning agent, with the balance being water.

[0064] In cosmetic compositions, modified nano-titanium dioxide, as a core sunscreen ingredient, possesses specific grain size, shape, and surface coating structure, enabling it to efficiently scatter and absorb ultraviolet rays, significantly increasing the sun protection factor (SPF) of the cosmetic composition. The surface of modified nano-titanium dioxide undergoes organic coating treatment, resulting in good hydrophobicity and uniform dispersion in oily emollients without producing a grainy feel. Simultaneously, modified nano-titanium dioxide works synergistically with skin feel improvers to enhance product spreadability and texture. Both inorganic and organically coated modified nano-titanium dioxide exhibit high stability under various environmental conditions. Its excellent dispersibility, aided by suspending agents and stabilizers, prevents product sedimentation and stratification during storage, maintaining a homogeneous and stable state.

[0065] In some embodiments, the cosmetic composition comprises 1-15% by mass of modified nano-titanium dioxide, 40-70% by mass of emollient, 2-6% by mass of emulsifier, 1-6% by mass of moisturizer, 0.1-1.5% by mass of dispersant, 1-4% by mass of suspending agent, 0.5-3% by mass of film-forming agent, 0.2-1.2% by mass of stabilizer, 0.2-0.8% by mass of preservative, 0.2-0.8% by mass of antioxidant, 1-8% by mass of skin feel improver, 1-6% by mass of skin conditioning agent, and the balance being water.

[0066] In some embodiments, the cosmetic composition comprises 3-15% by mass of modified nano-titanium dioxide, 50-70% by mass of emollient, 4-5% by mass of emulsifier, 3-5% by mass of moisturizer, 0.3-1.5% by mass of dispersant, 2-3% by mass of suspending agent, 1-2% by mass of film-forming agent, 0.5-1% by mass of stabilizer, 0.4-0.7% by mass of preservative, 0.4-0.7% by mass of antioxidant, 2-5% by mass of skin feel improver, 3-5% by mass of skin conditioning agent, and the balance being water.

[0067] The emollient is selected from one or more of the following: C12-15 benzoate, dioctyl carbonate, phenylethyl benzoate, triglyceride (ethylhexanoate), caprylic / capric triglyceride, diethylhexyl sebacate, propylheptaethyl caprylate, isononyl isononanoate, diisopropyl sebacate, dibutyl adipate, coconut oil alcohol caprylate / capric ester, butylene glycol dicaprylate / dicapric ester, diisopropyl adipate, lauryl lactate, butyl octyl salicylate, neopentyl glycol di(ethylhexanoate), polydimethylsiloxane, cetyl polydimethylsiloxane, tridecyl trimellitate, dioctyl ether, or isododecane.

[0068] The emulsifier is selected from one or more of PEG-9 polydimethylsiloxane, PEG-10 polydimethylsiloxane, polyglycerol-3 diisostearate, polyglycerol-2 dihydroxystearate, lauryl PEG-10 tris(trimethoxy)silyl ethyl polydimethylsiloxane, cetyl PEG / PPG-10 / 1 polydimethylsiloxane, or polyglycerol-4 diisostearate / polyhydroxystearate / sebacate.

[0069] The humectant is selected from one or more of glycerin, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diglycerides, polyglycerol-3, glyceryl polyether-26, or dipropylene glycol.

[0070] The dispersant is selected from polyhydroxystearic acid, polyglycerol-6 polyricinoleate, or polyglycerol-2 triisostearate.

[0071] The suspending agent is selected from distearate dimethylammonium lithium montmorillonite, silachlor bentonite, or silachlor hydropyrite.

[0072] The film-forming agent is selected from one or more of the following: polydimethylsiloxane / acrylate / polytrimethylsiloxane methacrylate copolymer, trimethylsiloxydecanoate, triacontyl PVP, trimethylpentanediol / adipic acid / glycerol polymer, polyC10-30 alkanol acrylate, hydrogenated dioleoyl carbonate, or dimethyl carbonate copolymer.

[0073] The stabilizer is selected from sodium chloride, sodium citrate, or magnesium sulfate.

[0074] The preservative is selected from 1,2-hexanediol, phenoxyethanol, chlorophenoxyethanol, p-hydroxyacetophenone, or capryloyl hydroxamic acid.

[0075] The antioxidant is selected from tocopherol or tocopherol acetate.

[0076] The skin feel improver is selected from silica, polymethylsilsesquioxane, HDI / trimethylolhexyl lactone crosspolymer, methyl methacrylate crosspolymer, or aluminum starch octenyl succinate.

[0077] The skin conditioning agent is selected from bisabolol, turmeric root extract, saffron flower extract, centella asiatica extract, dipotassium glycyrrhizate, nicotinamide, or glycyrrhetinic acid stearate.

[0078] In some embodiments, this application also provides the application of the modified nano-titanium dioxide described in the above embodiments or the modified nano-titanium dioxide prepared by the methods described in the above embodiments in sunscreen cosmetics to increase the SPF value. The modified nano-titanium dioxide with a grain size of 12-16 nm works synergistically with dispersants, emulsifiers, and other ingredients to ensure uniform dispersion in the cosmetic system. Good dispersibility allows the modified nano-titanium dioxide to fully exert its scattering and absorption effects on ultraviolet rays, thereby improving the sun protection effect and increasing the SPF value.

[0079] In some embodiments, this application also provides the application of the modified nano-titanium dioxide described in the above embodiments or the modified nano-titanium dioxide prepared by the methods described in the above embodiments in increasing the hydrophobicity of sunscreen cosmetics. In the preparation process of modified nano-titanium dioxide, organic coatings with long-chain hydrophobic structures, such as stearic acid, stearate, and isostearic acid, are selected to coat the titanium dioxide. The long-chain alkyl portions of these organic coatings can form a hydrophobic layer on the surface of titanium dioxide, changing its original hydrophilic surface properties. Furthermore, the inorganic coating layer itself can also improve the surface properties of titanium dioxide to a certain extent, providing a better foundation for subsequent organic coating, which helps to increase hydrophobicity, thereby effectively improving dispersibility in sunscreen cosmetics, further enhancing the sun protection effect, and increasing the SPF.

[0080] The modified nano-titanium dioxide provided in this application has smaller major and minor axes and smaller grain size. According to Rayleigh scattering theory, the grain size of this titanium dioxide is much smaller than 1 / 10 of the incident ultraviolet wavelength, which can more effectively block ultraviolet rays and improve sun protection performance. The rod-shaped titanium dioxide with a major-to-minor axis ratio of 3.5-4.2:1 can form a denser and more effective ultraviolet scattering network when arranged compared to other shapes of titanium dioxide. Rod-shaped titanium dioxide with different orientations can scatter ultraviolet rays from multiple angles, further enhancing the shielding effect. The first coating layer formed by the inorganic coating can improve the surface properties of titanium dioxide, reduce the negative impact of photocatalytic activity, and enhance the reflection and scattering ability of ultraviolet rays. The second coating layer of organic coating can further optimize the dispersibility of titanium dioxide in oil-based systems, allowing it to be more evenly distributed in sunscreen cosmetics, improving the absorption and scattering efficiency of ultraviolet rays, thereby enhancing the overall sun protection effect.

[0081] Preparation of modified nano titanium dioxide

[0082] Preparation Example

[0083] In the following examples, the prepared nanoscale titanium dioxide bulk is in powder form, therefore, in the following preparation examples, the titanium dioxide bulk is referred to as titanium dioxide raw powder.

[0084] 1. Preparation of titanium dioxide raw powder:

[0085] Weigh out a certain amount of sodium hydroxide and titanium tetrachloride (2.5 kg), and add them separately to deionized water to prepare 12 wt% sodium hydroxide aqueous solution and 15 wt% titanium tetrachloride aqueous solution. Place 5 kg of the 12 wt% sodium hydroxide solution in a reaction vessel, heat to 40°C, and add the 15 wt% titanium tetrachloride aqueous solution dropwise while stirring until the pH of the system is neutral. Stop the dropwise addition, heat the system to 95°C, and continue to add the 15% titanium tetrachloride aqueous solution dropwise. After the addition is complete, continue to react at 95°C for 2 hours to obtain a rutile nano-titanium dioxide dispersion. Add sodium hydroxide solution to adjust the pH of the rutile nano-titanium dioxide dispersion to neutral, filter the dispersion, wash with deionized water, and dry to obtain 1.04 kg of rutile titanium dioxide raw powder.

[0086] 2. Inorganic coating:

[0087] The above-mentioned rutile nano-titanium dioxide powder (1 kg) and sodium hexametaphosphate (30 g) were mixed evenly in water, controlling the titanium dioxide mass fraction to 15%, and then thoroughly dispersed by ball milling. The dispersion was then transferred to a reaction vessel and heated to 60–100 °C. A 150 g / L sodium aluminate aqueous solution (650 g) was added, and the pH was adjusted to 5–7 with hydrochloric acid. The mixture was then kept at this temperature for 30 minutes to mature. After cooling to below 30 °C, the mixture was thoroughly filtered and washed to obtain inorganically coated titanium dioxide particles.

[0088] 3. Organic coating:

[0089] The filter cake containing inorganically coated titanium dioxide microparticles was redispersed in deionized water, maintaining a titanium dioxide mass fraction of 10%. The dispersion temperature was increased to 70–95°C, followed by the addition of sodium stearate (110 g), and maturation continued for 30 minutes. After the reaction was complete, hydrochloric acid solution was added to adjust the pH to neutral. The dispersion was thoroughly filtered and washed. The cleaned filter cake was dried at 120°C for 15 hours and then pulverized to obtain surface-treated modified nano-titanium dioxide with a specific grain size. Figure 1 This is an electron microscope image of the modified nano-titanium dioxide prepared in this preparation example.

[0090] The testing methods used in this preparation example are as follows:

[0091] (I) Grain Size Measurement Methods

[0092] The grain size of the titanium dioxide microparticle sample was analyzed using X-ray diffraction (XRD).

[0093] The grain size can be calculated using the Scherrer formula D = 0.89 × γ / (β × cosθ).

[0094] In the formula:

[0095] D is the grain size (nm), γ is the X-ray wavelength, β is the full width at half maximum (FWHM), and θ is the diffraction angle.

[0096] (II) Methods for measuring major and minor diameters

[0097] The titanium dioxide microparticle sample was photographed using a transmission electron microscope (TEM). Particles with clear boundaries were selected (no less than 100, and preferably 200). The major and minor diameters of each particle were measured, and the arithmetic mean was taken to obtain the average major diameter d1 and the average minor diameter d2.

[0098] The ratio of the average major diameter d1 to the average minor diameter d2 is the major-minor diameter ratio.

[0099] (III) Method for detecting aluminum hydroxide coating amount

[0100] Titanium dioxide microparticle samples were digested with concentrated sulfuric acid and ammonium sulfate, and then analyzed using inductively coupled plasma atomic emission spectrometry (ICP). The mass fraction of aluminum hydroxide [ω(Al(OH)3)], expressed as a percentage, was calculated using the following formula: ω(Al(OH)3)=ω(Al)×2.891.

[0101] In the formula:

[0102] ω(Al) represents the percentage aluminum content of the sample obtained from instrumental analysis;

[0103] 2.891 is the conversion factor for aluminum to aluminum hydroxide.

[0104] (iv) Stearic acid coating amount detection method

[0105] The weight loss upon ignition (2g titanium dioxide microparticle sample, ignited at 800℃ to constant weight) was determined, and the weight loss upon drying (1g sample, dried at 105℃ for 3h) and the water loss of aluminum hydroxide (aluminum hydroxide result divided by 2.89) were deducted.

[0106] Five batches of modified nano-titanium dioxide were prepared using the same method, differing only in the mass fractions of aluminum hydroxide and stearic acid (see Table 1).

[0107] Batch 1 is named CS-NT-24-07-0001-01, with a grain size of 14.65 nm, a major axis d1 of 34.25 nm, a minor axis d2 of 8.52 nm, an aspect ratio of 4.02, an aluminum hydroxide mass fraction of 7.7%, and a stearic acid mass fraction of 8.3%.

[0108] Batch 2 is named CS-NT-25-07-0001-01, with a grain size of 14.01 nm, a major axis d1 of 36.74 nm, a minor axis d2 of 8.91 nm, an aspect ratio of 4.12, an aluminum hydroxide mass fraction of 7.7%, and a stearic acid mass fraction of 8.8%.

[0109] Batch 3, named CS-NT-25-07-0002-01, has a grain size of 14.22 nm, a major axis d1 of 30.63 nm, a minor axis d2 of 7.89 nm, an aspect ratio of 3.88, an aluminum hydroxide mass fraction of 7.4%, and a stearic acid mass fraction of 7.7%.

[0110] Batch 4, named CS-NT-25-07-0003-01, has a grain size of 14.89 nm, a major axis d1 of 34.63 nm, a minor axis d2 of 8.71 nm, an aspect ratio of 3.98, an aluminum hydroxide mass fraction of 7.5%, and a stearic acid mass fraction of 7.7%.

[0111] Batch 5, named CS-NT-25-07-0004-01, has a grain size of 14.81 nm, a major axis d1 of 33.14 nm, a minor axis d2 of 8.40 nm, an aspect ratio of 3.94, an aluminum hydroxide mass fraction of 7.5%, and a stearic acid mass fraction of 7.7%.

[0112] Table 1

[0113]

[0114] Comparative Example 1

[0115] 1. Preparation of titanium dioxide raw powder:

[0116] Weigh out a certain amount of sodium hydroxide and titanium tetrachloride (2.5 kg), and add them separately to deionized water to prepare 12 wt% sodium hydroxide aqueous solution and 15 wt% titanium tetrachloride aqueous solution. Place 5 kg of the 12 wt% sodium hydroxide solution in a reaction vessel, heat to 40°C, and add the 15 wt% titanium tetrachloride aqueous solution dropwise while stirring until the pH of the system is neutral. Stop the dropwise addition, heat the system to 95°C, and continue to add the 15% titanium tetrachloride aqueous solution dropwise. After the addition is complete, continue to react at 95°C for 2 hours to obtain a rutile nano-titanium dioxide dispersion. Add sodium hydroxide solution to adjust the pH of the rutile nano-titanium dioxide dispersion to neutral, filter the dispersion, wash thoroughly with deionized water, and dry to obtain 1.04 kg of rutile nano-titanium dioxide raw powder.

[0117] 2. Inorganic coating:

[0118] The above-mentioned rutile nano-titanium dioxide powder (1 kg) and sodium hexametaphosphate (30 g) were mixed evenly in water, controlling the titanium dioxide content to 15%, and then thoroughly dispersed by ball milling. The dispersion was then transferred to a reaction vessel and heated to 60–100 °C. A 150 g / L sodium aluminate aqueous solution (650 g) was added, and the pH was adjusted to 5–7 with hydrochloric acid. The mixture was then kept at this temperature for 30 minutes to mature.

[0119] 3. Organic coating:

[0120] Adjust the temperature of the reaction system in step 2 to 70–95°C, then add sodium stearate (110 g) and continue aging for 30 minutes. After the reaction is complete, add hydrochloric acid solution to adjust the pH to neutral. Filter and wash the dispersion thoroughly. Dry the cleaned filter cake at 120°C for 15 hours, then pulverize it to obtain modified nano-titanium dioxide.

[0121] Referring to Table 2, the batch name of the modified nano-titanium dioxide particles prepared in this comparative example is D-CS-NT-0001-01, the grain size is 15.05 nm, the major axis d1 is 33.28 nm, the minor axis d2 is 8.21 nm, the aspect ratio is 4.05, the mass fraction of aluminum hydroxide is 7.6%, and the mass fraction of stearic acid is 8.0%.

[0122] Table 2

[0123]

[0124] Comparative Example 2

[0125] The titanium dioxide used in this comparative example was purchased from Tayca Corporation of Japan, batch number MT-100TV-3230229.

[0126] Preparation of cosmetic compositions

[0127] Example 1

[0128] Weigh out polyhydroxystearic acid, isononyl isononanoate, cetyl polydimethylsiloxane, butyl octyl salicylate, lauryl PEG-10 tris(trimethoxy)silyl ethyl polydimethylsiloxane, polyglycerol-3 diisostearate, propyl heptyl octanoate, and polydimethylsiloxane / acrylate / polytrimethylsiloxane methacrylate copolymer into a 250 mL beaker. Heat in a water bath at 85 °C for 10 min, stirring until dissolved and homogeneous. Add modified nano-titanium dioxide, heat at 85 °C for 5 min, stir until homogeneous, and homogenize at 4400 rpm (IKA) for 3 min. Add polydimethylsiloxane, isododecane / distearate dimethylammonium lithium montmorillonite / propylene glycol carbonate, isododecane, silica, bisabolol, and tocopheryl acetate, stir until homogeneous, and homogenize at 4400 rpm (IKA) for 2 min to obtain slurry 1. Before adding isododecane / distearate dimethylammonium lithium montmorillonite / propylene glycol carbonate, it is necessary to disperse it with isododecane in advance. The specific method is to mix isododecane / distearate dimethylammonium lithium montmorillonite / propylene glycol carbonate with isododecane evenly, and then homogenize it at 5000 rpm for 2 min.

[0129] Caprylyl glycol / phenoxyethanol, water, glycerin, and magnesium sulfate were weighed into a 100 mL beaker and heated in a water bath at 85 °C for 30 min to obtain slurry 2. Slurry 2 was slowly added dropwise to slurry 1 at 300 (1 KA) rpm. The mixture was then homogenized at 4000 rpm for 2 min and discharged to obtain the cosmetic composition.

[0130] In this embodiment, the following ingredients are used: 1g polyhydroxystearic acid, 10g isononyl isononanoate, 1g cetyl polydimethylsiloxane, 5g butyl octyl salicylate, 3g lauryl PEG-10 tris(trimethoxy)silyl ethyl polydimethylsiloxane, 1g polyglycerol-3 diisostearate, 7g propyl heptyl octanoate, 2g polydimethylsiloxane / acrylate / polytrimethylsiloxane methacrylate copolymer, 1g modified nano titanium dioxide, 13.5g polydimethylsiloxane, 3g isododecane / distearate dimethylammonium lithium montmorillonite / propylene glycol carbonate, 5g isododecane, 4g silica, 0.2g bisabolol, 0.5g tocopheryl acetate, 0.4g octyl glycol / phenoxyethanol, 37.4g water, 4g glycerin, and 1g magnesium sulfate.

[0131] Example 2

[0132] The preparation method of the cosmetic composition prepared in this embodiment is the same as that in Example 1, except that the amount of modified nano titanium dioxide and water added is different. In this embodiment, the amount of modified nano titanium dioxide is 3g and the amount of water is 35.4g.

[0133] Example 3

[0134] The preparation method of the cosmetic composition prepared in this embodiment is the same as that in Example 1, except that the amount of modified nano titanium dioxide and water added is different. In this embodiment, the amount of modified nano titanium dioxide is 5g and the amount of water is 33.4g.

[0135] Example 4

[0136] The preparation method of the cosmetic composition prepared in this embodiment is the same as that in Example 1, except that the amount of modified nano titanium dioxide and water added is different. In this embodiment, the amount of modified nano titanium dioxide is 8g and the amount of water is 30.4g.

[0137] Example 5

[0138] The preparation method of the cosmetic composition prepared in this embodiment is the same as that in Example 1, except that the amount of modified nano titanium dioxide and water added is different. In this embodiment, the amount of modified nano titanium dioxide is 10g and the amount of water is 28.4g.

[0139] Example 6

[0140] The preparation method of the cosmetic composition prepared in this embodiment is the same as that in Example 1, except that the amount of modified nano titanium dioxide and water added is different. In this embodiment, the amount of modified nano titanium dioxide is 15g and the amount of water is 23.4g.

[0141] The component amounts for each embodiment are shown in Table 3.

[0142] Table 3

[0143]

[0144]

[0145] Example 1: Sunscreen Comparison Experiment

[0146] Modified nano-titanium dioxide with batch numbers CS-NT-25-07-0001-01 (batch 2), CS-NT-25-07-0002-01 (batch 3), and MT-100TV-3230229 (comparative example 2) were used to prepare cosmetic compositions according to the formulations and processes of Examples 1 to 6, totaling 18 parts, i.e., 6 samples from each batch. The dimensions of the titanium dioxide of CS-NT-25-07-0001-01 (batch 2), CS-NT-25-07-0002-01 (batch 3), and MT-100TV-3230229 (comparative example 2) are shown in Table 4.

[0147] Table 4

[0148]

[0149] Two hours after the cosmetic composition was prepared, the sun protection value of 18 samples was tested. The test results are shown in Tables 5 and 6.

[0150] Sun protection factor (SPF) testing method:

[0151] Instruments: UV-2000s ultraviolet transmittance analyzer, PMMA plate (size: 5cm×5cm, company: Kunststoffe-Verarbeitung GmbH & Co. KG.).

[0152] Table 5

[0153] SPF value MT-100TV-3230229 CS-NT-25-07-0001-01 CS-NT-25-07-0002-01 Example 1 4.21 4.32 4.29 Example 2 7.62 8.46 9.19 Example 3 13.38 16.35 18.14 Example 4 19.21 24.26 29.78 Example 5 25.97 49.45 37.51 Example 6 37.19 60.30 65.77

[0154] Table 6

[0155] UVAPF value MT-100TV-3230229 CS-NT-25-07-0001-01 CS-NT-25-07-0002-01 Example 1 1.43 1.52 1.50 Example 2 2.16 2.53 2.50 Example 3 3.10 3.43 3.72 Example 4 4.15 4.48 5.44 Example 5 5.09 6.03 6.47 Example 6 6.39 7.84 9.36

[0156] As shown in Tables 5 and 6, batch CS-NT-25-07-0001-01 (batch 2), with the same addition amount (3-15%), showed an SPF value increase of 11-90% and a UVAPF value increase of 8-23% compared to the commercially available product MT-100TV-3230229 (comparative example 2). Batch CS-NT-25-07-0002-01 (batch 3), with the same addition amount (3-15%), showed an SPF value increase of 21-77% and a UVAPF value increase of 16-46% compared to the commercially available product MT-100TV-3230229 (comparative example 2). Therefore, the modified nano-titanium dioxide prepared in this application can achieve the same or better sun protection effect with a smaller addition amount compared to commercially available products, exhibiting unexpectedly excellent sun protection performance.

[0157] Example 2: Hydrophobicity Experiment

[0158] The hydrophobicity test was conducted on titanium dioxide samples from batches 1 to 5, and comparative examples 1 and 2. The specific results are shown in Table 7.

[0159] The test method is as follows: Add 95 mL of ultrapure water to a 100 mL stoppered graduated cylinder, accurately weigh 2 g of sample powder, add it to the stoppered graduated cylinder, and tighten the stopper. Shake the cylinder up and down at a relatively large amplitude 50 times at a uniform speed (controlling the oscillation frequency at 50 times / min and the amplitude at 180°). Then place the stoppered graduated cylinder on the table and let it stand for 30 minutes. Observe in a dark chamber to see if there is obvious sediment at the bottom and whether the water layer is clear. Then take the above lower aqueous phase solution into a 1 cm cuvette, using purified water as a blank, and measure the absorbance A at 600 nm using a UV spectrophotometer.

[0160] The transmittance is calculated using the formula: T = 10 - A × 100%

[0161] Table 7

[0162] Batch number Light transmittance T / % CS-NT-24-07-0001-01 99.31% CS-NT-25-07-0001-01 99.31% CS-NT-25-07-0002-01 99.08% CS-NT-25-07-0003-01 98.85% CS-NT-25-07-0004-01 99.31% D-CS-NT-0001-01 80.53% MT-100TV-3230229 81.09%

[0163] As shown in Table 7, the modified nano-titanium dioxide of this application has excellent hydrophobicity compared with comparative example D-CS-NT-0001-01 and commercially available product MT-100TV-3230229.

[0164] Example 3: Contact Angle Experiment

[0165] The contact angle test was conducted on titanium dioxide samples from batches 1 to 5, and comparative examples 1 and 2. The specific results are shown in Table 8.

[0166] The test method is as follows: The powder to be tested is compressed into tablets under the same pressure for later use. Water is added to a syringe, which is then inverted and bounced to expel air bubbles. The syringe is then placed in an automatic dropping stage for calibration. A Kruss DSA25 micrometer is used to test the contact angle of the hydrophobic powder using the seated drop method. A larger contact angle indicates better hydrophobicity.

[0167] Table 8

[0168] Batch number Contact angle CS-NT-24-07-0001-01 146.69(±2.66) CS-NT-25-07-0001-01 148.71(±2.03) CS-NT-25-07-0002-01 146.83(±2.53) CS-NT-25-07-0003-01 147.12(±1.73) CS-NT-25-07-0004-01 140.78(±2.55) D-CS-NT-0001-01 136.89(±2.23) MT-100TV-3230229 133.72(±0.77)

[0169] As shown in Table 8, the modified nano-titanium dioxide provided in this application has a larger contact angle and better hydrophobic properties compared with comparative example D-CS-NT-0001-01 and commercially available product MT-100TV-3230229.

[0170] Hydrophobicity and contact angle experiments show that the modified nano-titanium dioxide after inorganic coating and thorough washing has higher light transmittance, larger contact angle, and significantly better hydrophobicity than the incompletely washed product.

[0171] The modified nano-titanium dioxide prepared in batches 1 to 5 of Preparation Example 1 of this application, through thorough washing of the inorganically coated filter cake in the preparation process, reduces the salt content in the titanium dioxide product, thereby improving the hydrophobicity of the titanium dioxide. Simultaneously, the washed surface is more conducive to the directional alignment of long-chain hydrophobic groups of stearic acid, forming a complete and effective hydrophobic layer, thus improving the hydrophobicity of the product.

[0172] This application allows for microscopic control of the grain size, major axis, minor axis, and aspect ratio of titanium dioxide, thereby obtaining titanium dioxide with a high sun protection value. The modified nano-titanium dioxide provided in this application exhibits better hydrophobicity and dispersibility due to its more complete surface coating. Good dispersibility minimizes the aggregation of titanium dioxide, resulting in superior sun protection. Furthermore, because this modified nano-titanium dioxide possesses excellent hydrophobicity and UV absorption, oleophilicity, and good dispersibility in oily solvents, its application in personal sun protection products can improve sun protection performance while also ensuring a pleasant user experience.

[0173] As can be seen from the above embodiments, this application provides a modified nano-titanium dioxide for cosmetics, a preparation method, a cosmetic composition, and an application. The modified nano-titanium dioxide includes a nano-sized titanium dioxide body and a first coating layer and a second coating layer sequentially coating the nano-sized titanium dioxide body. The first coating layer is an inorganic coating, and the second coating layer is an organic coating. The grain size of the modified nano-titanium dioxide is 12-16 nm, and the modified nano-titanium dioxide has a rod-like structure with an aspect ratio of 3.5-4.2:1. By using 12-16 nm nano-titanium dioxide, this application can more effectively block ultraviolet rays and improve sun protection performance. Compared with particles of other shapes, the rod-like titanium dioxide particles with an aspect ratio of 3.5-4.2:1 can form a denser and more effective ultraviolet scattering network when arranged. Rod-like particles with different orientations can scatter ultraviolet rays from multiple angles, further enhancing the shielding effect against ultraviolet rays. The sequential coating with inorganic and organic coatings alters the original hydrophilic surface properties of titanium dioxide, giving the modified nano-titanium dioxide excellent hydrophobicity. The dual effect of the inorganic and organic coatings effectively improves the dispersibility of titanium dioxide in the medium. The modified nano-titanium dioxide for cosmetics provided in this application exhibits excellent hydrophobicity and UV absorption, lipophilicity, and good dispersibility in oily solvents, enhancing the sun protection performance of cosmetics while also providing a superior user experience.

[0174] Similar parts between the embodiments provided in this application can be referred to mutually. The specific implementation methods provided above are only a few examples under the overall concept of this application and do not constitute a limitation on the scope of protection of this application. For those skilled in the art, any other implementation methods extended from the solution of this application without creative effort shall fall within the scope of protection of this application.

Claims

1. A modified nano-titanium dioxide for cosmetic use, characterized in that, The modified nano-titanium dioxide comprises a nano-scale titanium dioxide body, and a first coating layer and a second coating layer sequentially coated on the nano-scale titanium dioxide body, wherein the first coating layer is an inorganic coating material, and the second coating layer is an organic coating material; The modified nano-titanium dioxide has a grain size of 12 to 16 nm, the modified nano-titanium dioxide has a rod-like structure, and the aspect ratio of the modified nano-titanium dioxide is 3.5 to 4.2:

1.

2. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The long diameter d1 of the rod-like structured modified nano-titanium dioxide is in the range of 30<d1≤37 nm, and the short diameter d2 of the rod-like structured modified nano-titanium dioxide is in the range of 7<d2≤10 nm.

3. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The mass fraction of the inorganic coating material is 7 to 8%, and the mass fraction of the organic coating material is 7 to 9%.

4. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The modified nano-titanium dioxide has a grain size of 14 to 15 nm.

5. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The crystal form of the modified nano-titanium dioxide is anatase, rutile or amorphous.

6. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The inorganic coating material is selected from one or more of aluminum hydroxide, aluminum oxide, silicon oxide or zirconium oxide.

7. The modified nano-titanium dioxide for cosmetic use according to claim 1, characterized in that, The organic coating material is selected from stearic acid, isostearic acid, palmitic acid or behenic acid.

8. A method for preparing modified nano-titanium dioxide for cosmetic use, characterized in that, The modified nano-titanium dioxide is the modified nano-titanium dioxide as described in any one of claims 1 to 7, and the method comprises: At 35 to 45°C, an aqueous titanium tetrachloride solution is added dropwise to an alkaline solution until the pH value of the reaction solution is neutral, and the dropwise addition of the aqueous titanium tetrachloride solution is suspended; the alkaline solution is an aqueous alkali metal hydroxide solution with a mass concentration of 12 to 15%; The reaction solution is heated to 85 to 95°C, the aqueous titanium tetrachloride solution is further added thereto, and then the mixture is subjected to a heat preservation reaction to obtain a nano-scale titanium dioxide dispersion liquid; An alkaline solution is added to the nano-scale titanium dioxide dispersion liquid to adjust the pH value of the dispersion liquid to neutral, followed by filtering, washing and drying to obtain the nano-scale titanium dioxide body; The nano-scale titanium dioxide body is mixed with an aqueous solution of a water-soluble inorganic coating metal salt to carry out a coating reaction, followed by filtering and washing to obtain inorganic coated titanium dioxide particles; The inorganic coated titanium dioxide particles are mixed with an organic coating material or a salt thereof to carry out a coating reaction, followed by filtering, washing and drying to obtain the modified nano-titanium dioxide.

9. The method according to claim 8, characterized in that, After the nano-scale titanium dioxide body is mixed with the aqueous solution of the water-soluble inorganic coating metal salt to carry out the coating reaction, the steps comprise: After the reaction is finished, the reacted solution is cooled to room temperature and then subjected to multiple filtration and washing to obtain the inorganic coated titanium dioxide particles.

10. A cosmetic composition, characterized in that, The cosmetic composition comprises: The modified nano-titanium dioxide according to any one of claims 1 to 7, an emollient, an emulsifier, a humectant, a dispersant, a suspending agent, a film-forming agent, a stabilizer, a preservative, an antioxidant, a skin feel improver, a skin conditioning agent and water; wherein the mass fraction ranges of each component in the cosmetic composition are: 1 to 25% of modified nano-titanium dioxide, 26 to 70% of emollient, 1 to 8% of emulsifier, 0 to 8% of humectant, 0 to 2.5% of dispersant, 0 to 5% of suspending agent, 0 to 5% of film-forming agent, 0 to 1.5% of stabilizer, 0 to 1% of preservative, 0 to 1% of antioxidant, 0 to 10% of skin feel improver, 0 to 8% of skin conditioning agent, with the balance being water.

11. The application of the modified nano-titanium dioxide according to any one of claims 1-7 or the modified nano-titanium dioxide prepared by the method of claim 8 in sunscreen cosmetics to increase the sun protection value.

12. The application of the modified nano-titanium dioxide according to any one of claims 1-7 or the modified nano-titanium dioxide prepared by the method of claim 8 in sunscreen cosmetics to increase hydrophobicity.